2019
DOI: 10.5606/archrheumatol.2019.7249
|View full text |Cite
|
Sign up to set email alerts
|

Familial Mediterranean Fever and Multiple Sclerosis Successfully Treated With Interferon Beta-1a: A Case Report

Abstract: Familial Mediterranean fever (FMF) is an autosomal recessive autoinflammatory disorder. It is characterized by recurrent attacks of fever, peritonitis, pleuritis, and synovitis and common in Mediterranean people including Turks, Arabs, Armenians, and non-Ashkenazi Jews. 1 The responsible gene for FMF is MEFV located on chromosome 16p. Multiple sclerosis (MS) is the most common demyelinating disease of central nervous system. MS is characterized by inflammation and demyelination and caused by several environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…IL‐1 targeting therapy (anakinra or canakinumab) has been successful in managing both overlap conditions in two case reports, while a third report described relapse freedom on colchicine and rituximab using clinical and MRI follow‐up data. 11 , 12 , 13 A case series of ocrelizumab treatment for 18 months in 11 people with secondary progressive MS showed reduction in both FMF and MS attacks. 14 …”
Section: Discussionmentioning
confidence: 99%
“…IL‐1 targeting therapy (anakinra or canakinumab) has been successful in managing both overlap conditions in two case reports, while a third report described relapse freedom on colchicine and rituximab using clinical and MRI follow‐up data. 11 , 12 , 13 A case series of ocrelizumab treatment for 18 months in 11 people with secondary progressive MS showed reduction in both FMF and MS attacks. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Paradoxically, in addition to its antiviral effect, IFN-I, particularly IFN-β, can also exert anti-inflammatory effects by enhancing the production of immunosuppressive cytokine IL-10, enhancing the expression of SOCS-1, downregulating matrix metalloproteinase–9 (MMP-9), or inducing IFI16-mediated inflammasome inhibition [ 26 ] (graphical abstract). Therefore, IFN-Is have been widely applied to treat autoimmune and inflammatory diseases, such as multiple sclerosis (MS) [ 5 ], familial Mediterranean fever (FMF) [ 43 ], and Behcet’s syndrome [ 44 ]. In this study, our transcription profile assay indicated that Poly6 treatment of SARS-CoV-2-infected Calu-3 cells led to the upregulation of the genes STAT1 , IRF3 , IRF9 , JAK1 , and IFI16 ( Figure 4 D and Figure S4 ) and of two immunosuppressive molecules, IL-10 and SOCS-1, but to the downregulation of pro-inflammatory genes such as IL-6 and IL-1β .…”
Section: Discussionmentioning
confidence: 99%